Structural determination of three neutral oligosaccharides in bovine (Holstein-Friesian) colostrum, including the novel trisaccharide; GalNAcαl-3Galβ1-4Glc - Tadasu Urashima; Tadao Saito; Kenzi Ohmisya; Keiichi Shimazaki (Biochimica et biophysica acta. General subjects, 1991)
Two trisaccharides, and a pentasaccharide were obtained from bovine colostrum. Their chemical structures were determined by using methylation and 13C-NMR analyses as follows: GalNacα1-3Galβ1-4Glc, Galα-1-3Galβ1-4Glc, Galβ1-3[Galβ1-4GlcNAcβ1-6]Galβ1-4Glc. GalNAcα1-3Galβ1-4Glc, which was identified in this study, is a novel oligosaccharide from natural sources. Galα1-3Galβ1-4Glc and Galβ1-3[Galβ1-4GlcNAcβ1-6]Galβ1-4Glc (lacto-N-novopentaose) have been already found in ovine colostrum, and in horse colostrum and marsupial milk, respectively.